Pedagogies of engagement use in postsecondary chemistry education in the United States: results from a national survey. Issue 1 (14th August 2020) - Raker, Jeffrey R.; Dood, Amber J.; Srinivasan, Shalini; Murphy, Kristen L.
Abstract : Pedagogies of engagement ( i.e., Peer-Led Teaming Learning, Problem-Based Learning, and Process-Oriented Guided Inquiry Learning) are active learning approaches used in postsecondary chemistry courses. In this study, we use data from a national survey of postsecondary chemistry instructors in the United States to estimate use of three pedagogies in the course for which the instructor feels they have the most control. We found that 16.6% of these faculties report they are implementing Peer-Led Team Learning (PLTL), 10.6% report implementing Problem-Based Learning (PBL), and 10.7% report implementing Process-Oriented Guided-Inquiry Learning (POGIL). We compare use of select teaching practices and other active learning strategies with implementation of PLTL, PBL, and POGIL. Additionally, we use items from the survey to understand course, institution, and instructor characteristics associated with use. Key findings include that lower-level courses and courses with large enrollments are the most likely places for PLTL to be implemented and that instructors who are not on the tenure track are more likely to implement PLTL and POGIL than tenured/tenure-track instructors. Instructors who report implementing PLTL and PBL have more student-centered beliefs about teaching and learning, while instructors who report implementing POGIL have more teacher-centered beliefs about learning, albeit all with small effect sizes. Implications are offered for how instructors, researchers, developers and disseminators of these pedagogies can use our results to inform their practices and efforts.